VUCA environment on project success: The effect of project management methods - Ralf Luis de Moura; Teresa Cristina Janes Carneiro; Taciana Lemos Dias (BBR: Brazilian Business Review)
Due to the ever-changing work environment in the age of digital transformation, project managers need to adapt to an environment which is volatile, uncertain, complex, and ambiguous (VUCA). Many organizations adopt management methods based on strict project management planning , assuming that they are the best way to succeed in any situation. However, projects may depend on flexibility to achieve success. This study aims to analyze the impact of adverse project environments on project success and the effect of the management method choice. A PLS-SEM model is tested on a survey of 332 project professionals. Findings showed that choosing a method that best fits the project's environment can help catch up on project success only when it undergoes frequent changes throughout its life cycle.